Extraction of Bioactive Compounds From Withania somnifera: The Biological Activities and Potential Application in the Food Industry: A Review - Siva Karthikeyan Singirala; Praveen Kumar Dubey; Swarup Roy (International Journal of Food Science)
As awareness of the link between diet and health grows, people are increasingly prioritizing functional foods that offer additional health benefits beyond basic nutrition. Ashwagandha, scientifically known as Withania somnifera (WS), is a perennial plant which belongs to the family Solanaceae, which grows abundantly in subtropical regions of the world. Ashwagandha is a renowned Ayurvedic herb with diverse applications in global dietary supplements and traditional medicines. It has extensive medicinal potential in traditional Indian systems such as (Ayurvedic, Unani, and Siddha) and contemporary medicine, recognized as the “Indian ginseng.” WS is a dietary additive composed of various phytochemicals and active compounds such as withanolides, polyphenols, flavonoids, alkaloids, which exhibit therapeutic properties, including anti-inflammatory, anticancer, antistress, antioxidant, antimicrobial, antidiabetic, cardioprotective, hypoglycemic, hepatoprotective, immunomodulatory, and rejuvenating effects. WS has been scientifically proven to be highly effective against numerous neurological and psychological disorders. The incorporation of ashwagandha into food enhances the biological activity of the food as well as enhances the functional properties, making it a valuable functional food with potential health benefits. This review provides an updated analysis of WS, emphasizing its bioactive compounds, extraction techniques, and functional food applications. Unlike previous studies that primarily focused on its medicinal properties, this review highlights integration into food systems, addressing technological challenges, stability, and commercial viability. Additionally, it compiles advancements in analytical techniques, offering insights into enhancing bioavailability and sensory optimization, thereby bridging traditional herbal use with modern food science.